2012
DOI: 10.1021/om300893q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Cationic Phosphine Gold(I) Enol Ether Complexes

Abstract: Cationic {[(t-Bu) 2 (o-biphenyl)P]Au(enol ether)} + SbF 6 − and {[(t-Bu) 3 P]Au(enol ether)} + SbF 6 − complexes were isolated and characterized by NMR spectroscopy and X-ray crystallography. For three of the four complexes characterized in the solid state, gold coordinates to the electronrich bond in a η 1 fashion, while a 2,3-dihydrofuran complex displays η 2 coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
11
34
0
Order By: Relevance
“…In our recent efforts to synthesize gold(I) enol ether complexes,7 we adopted a procedure of mixing phosphine gold(I) chlorides with AgSbF 6 in CH 2 Cl 2 followed by filtration through Celite. According to experimental procedures described in the literature, this was expected to coincide with an initial quantitative precipitation of solid AgCl and formation of R 3 PAu + SbF 6 − , which would remain in solution 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent efforts to synthesize gold(I) enol ether complexes,7 we adopted a procedure of mixing phosphine gold(I) chlorides with AgSbF 6 in CH 2 Cl 2 followed by filtration through Celite. According to experimental procedures described in the literature, this was expected to coincide with an initial quantitative precipitation of solid AgCl and formation of R 3 PAu + SbF 6 − , which would remain in solution 13.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Additionally, there is a growing trend toward the development of silver-free catalysts, due to the ambiguity of silver involvement and stoichiometry. [5,6] In our efforts to prepare mechanistically relevant gold complexes [7] from the preparative combination of phosphine gold chlorides and silver salts, we have encountered situations where the expectation of "quantitative precipitation of AgCl" [10a] was inconsistent with our observations. We thus sought to more carefully explore the solution chemistry of silver/gold mixtures.…”
Section: Introductionmentioning
confidence: 87%
“…The same asymmetry has been experimentally observed, too. [33] Finally, the vinyl ether can de-coordinate and be substituted by another molecule of alkyne. [34] From the structure of TS_attack, the experimentally observed anion effect (Figure 1) can be rationalized on the basis of the coordinating and basicity properties of the different anions.…”
mentioning
confidence: 99%
“…As expected, hydrogen bond acceptors with lower gold affinity (e.g., DMPU, DMF) [141][142][143][144][145][146][147][148] enhanced the rate of reaction (Scheme 14b), and ionic hydrogen bond acceptors (e.g., Bu4N Other research groups reported that certain compounds improved the chemical yields in selected gold catalyzed reactions. 153,154 One notable example is the …”
Section: Scheme 14 Additive Effects On Various Gold Catalyzed Reactisupporting
confidence: 64%